2020
DOI: 10.3390/jpm10030108
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics to Predict Tumor Therapy Response: A Focus on ATP-Binding Cassette Transporters and Cytochromes P450

Abstract: Pharmacogenomics is an evolving tool of precision medicine. Recently, due to the introduction of next-generation sequencing and projects generating “Big Data”, a plethora of new genetic variants in pharmacogenes have been discovered. Cancer resistance is a major complication often preventing successful anticancer treatments. Pharmacogenomics of both somatic mutations in tumor cells and germline variants may help optimize targeted treatments and improve the response to conventional oncological therapy. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 110 publications
2
27
0
Order By: Relevance
“…ABCC5 is also involved in the efflux of different anticancer drugs such as 6-MP, 6-TG, 5-FU, and their metabolites [14][15][16][17][18][19], and this efflux is often associated with drug resistance. Additionally, studies have shown that gene polymorphisms of ABC transporters An equal amount of cell lysate (20 μg of protein/lane) was analyzed using β-actin as the loading control (*p < 0.05, compared with non-MTA treatment group; #p < 0.05, compared with AdvCtrl group) influence protein expression and determine the efficacy of some anticancer agents [36,37], despite paradoxical results in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…ABCC5 is also involved in the efflux of different anticancer drugs such as 6-MP, 6-TG, 5-FU, and their metabolites [14][15][16][17][18][19], and this efflux is often associated with drug resistance. Additionally, studies have shown that gene polymorphisms of ABC transporters An equal amount of cell lysate (20 μg of protein/lane) was analyzed using β-actin as the loading control (*p < 0.05, compared with non-MTA treatment group; #p < 0.05, compared with AdvCtrl group) influence protein expression and determine the efficacy of some anticancer agents [36,37], despite paradoxical results in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…ABCC5 has also been shown to be involved in the e ux of many different anticancer drugs, for instance, 6-MP, 6-TG, 5-FU and its metabolites [10-12, 24, 25, 29], and this e ux was often considered to be associated with drug resistance. In addition, plenty of studies presented that the gene polymorphisms of ABC transporters in uence the proteins expressions and nally determine the e cacy of some anticancer agents [36,37] despite some paradoxical results in these studies were shown.…”
Section: Discussionmentioning
confidence: 99%
“…However, while this collection of evidence hints at a possible network of pathways connecting oxysterols to anti-cancer drugs via ABC transporters, the research is lacking in scope and detail and does not provide any concrete answers. Using and combining modern methods such as highthroughput RNA and DNA sequencing (transcriptomics and genomics, respectively), proteomics and metabolomics might be able to bring new light into the area of ABC transporters that have been studied for several decades, such as ABCB1, ABCC1, and ABCG2 (Robey et al, 2018), as well as the remaining 45 known human ABCs which have received little attention in comparison (Hlavac, Holy, & Soucek, 2020).…”
Section: Chemotherapymentioning
confidence: 99%